2007
DOI: 10.1029/2006jd007056
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated and water‐soluble organic aerosols in Tokyo

Abstract: [1] Submicron organic aerosol was measured simultaneously with an Aerodyne aerosol mass spectrometer (AMS) and a particle-into-liquid sampler (PILS) capable of measuring water-soluble organic carbon (WSOC) during the winter and summer of 2004 in Tokyo. Both techniques are being used to investigate the formation of secondary organic aerosol (SOA), and the combined data sets provide unique insights. In summer, about 80% (40-65%) of organic aerosols were oxygenated when scaled by total (carbon) mass concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

35
260
4
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 281 publications
(305 citation statements)
references
References 30 publications
(76 reference statements)
35
260
4
6
Order By: Relevance
“…Recent studies have compared real-time WSOC concentrations measured using particle-into-liquid sampler total organic carbon (PILS-TOC) data with the AMS-PMF-resolved factors, such as LVOOA, SVOOA, BBOA, and HOA. These studies have suggested that LVOOA and m/z 44 correlates well with WSOCs relative to other oxygenated factors [Kondo et al, 2007;Xiao et al, 2011;Sun et al, 2011;Timonen et al, 2013]. In this extended study, we used the AMS-PMF-resolved real-time LVOOA fraction as water-soluble organic aerosols to achieve CCN closure and better describe the hygroscopicity of the organic component of aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have compared real-time WSOC concentrations measured using particle-into-liquid sampler total organic carbon (PILS-TOC) data with the AMS-PMF-resolved factors, such as LVOOA, SVOOA, BBOA, and HOA. These studies have suggested that LVOOA and m/z 44 correlates well with WSOCs relative to other oxygenated factors [Kondo et al, 2007;Xiao et al, 2011;Sun et al, 2011;Timonen et al, 2013]. In this extended study, we used the AMS-PMF-resolved real-time LVOOA fraction as water-soluble organic aerosols to achieve CCN closure and better describe the hygroscopicity of the organic component of aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…The signal at m/z 44, which originates mainly from CO + 2 , is considered the most reliable marker of oxygenated organic aerosol (Zhang et al 2005b; and references therein). Previous studies showed that the increase in m/z 44 signal was often associated with photochemical processing of air masses (Takegawa et al 2006a(Takegawa et al , 2006bZhang et al 2005a), and that the m/z 44 signal correlated well with the mass concentrations of WSOC (Kondo et al 2007). Diacids are considered the major compounds that can contribute significantly to the m/z 44 signal, as well as ω-oxocarboxylic acids (ω-oxoacids) containing carboxyl and aldehyde groups.…”
Section: Introductionmentioning
confidence: 99%
“…They are emitted directly from combustion, industrial, and natural sources (primary) and/or formed through secondary processes such as homogeneous gas-phase and/or heterogeneous aerosol-phase oxidation (secondary) (Claeys et al, 2004;Koch et al, 2007;Schichtel et al, 2008). Although the primary sources such as biomass burning may be important for WSOC loadings , it is suggested that a major fraction of WSOC is from secondary organic aerosol (SOA) formation (Aggarwal and Kawamura, 2009;Kondo et al, 2007). Sullivan et al (2004) found correlated diurnal variations between ratio of WSOC/OC and O 3 in summer, indicating that a significant fraction of WSOC was originated from secondary formation.…”
Section: Introductionmentioning
confidence: 99%